Secoeudesma sesquiterpenes lactone A alleviates inflammation and offers adjuvant protection in severe infection of carbapenem-resistant Klebsiella pneumoniae. (24th April 2020) - Jiang, Xinru; Chen, Yijian; Liu, Dan; Shi, Ting; Cheng, Xiaodong; He, Weigang; Li, Yinhong; Ryffel, Bernhard; Zheng, Song Guo; Zheng, Yuejuan
Abstract: Ethnopharmacological relevance: Secoeudesma sesquiterpenes lactone A (SESLA) is a sesquiterpene compound isolated from Inula japonica Thunb. ( I. japonica ). It is an herb widely distributed in Asian countries often used for the treatment of various conditions including tumors, bronchitis and bacterial and viral infections. It has been reported that SESLA could significantly inhibit the production of nitric oxide (NO) by lipopolysaccharide (LPS) in Raw264.7 cells. However, the mechanism responsible for this anti-inflammatory role and its role in the treatment of antibiotic-resistant bacterial infection, e.g., carbapenem-resistant Klebsiella pneumoniae (CRKP), remain to be investigated. Aim of the study: This study was carried out to investigate the protective anti-inflammatory role and the underlying molecular mechanisms of SESLA in LPS or CRKP evoked inflammation. Materials and methods: ELISA and PCR were utilized to detect the expression of inflammatory mediators in LPS or heat-killed CRKP (HK CRKP)-stimulated immune cells containing different concentrations of SESLA. The protective role of SESLA was observed in mice challenged with a lethal dose of CRKP. Mice were intraperitoneally injected with CRKP to create a septic mouse model to evaluate the protective role of SESLA in vivo . Phosphorylated proteins, which represented the activation of signaling pathways, were examined by Western blot. Results: SESLA was showed to inhibit the expression of inflammatory mediators in various macrophages and dendritic cells upon stimulation of LPS or HK CRKP. It also facilitated phagocytosis of bacteria by Raw264.7 cells. The combined use of SELSA and the ineffective antibiotic, meropenem, increased the survival rate of CRKP infected mice from 25% to 50%. ERK, NF-κB and PI3K/Akt pathways accounted for the anti-inflammatory role of SESLA with the stimulation of LPS. Conclusion: According to the notable anti-inflammatory effect in vitro and its joint protective effects on a septic mouse model, SESLA might act as an adjuvant drug candidate for sepsis, even those caused by antibiotic-resistant bacteria, e.g., CRKP. Graphical abstract: Image 1 Highlights: Secoeudesma sesquiterpenes lactone A inhibits the production of inflammatory mediators in macrophages and dendritic cells in vitro. Secoeudesma sesquiterpenes lactone A could also promote the phagocytosis of bacteria by macrophages. SESLA inhibits inflammation, promotes the phagocytosis of bacteria, and protects CRKP infected mice together with ineffective antibiotic (MEM). ERK, NF-κB and PI3K/Akt pathways account for the anti-inflammatory role of secoeudesma sesquiterpenes lactone A.